2016
DOI: 10.1021/acsami.6b07943
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Formation of Stable Surface Relief Structures in Bisanthracene Films with Spatially Patterned Photopolymerization

Abstract: A facile method for the fabrication of a highly sensitive surface relief is demonstrated, which operates on the principle of spatially patterned photopolymerization-induced mass transport in the amorphous films of a series of bisanthracene compounds. The stability of the resultant colorless transparent relief structure is dramatically improved owing to the polymerization of the bisanthracene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…A similar molecular motion has been observed in the patterned exposure to cinnamate-containing polymeric films, which causes photo-cross-linking . The difference in the stiffness of the film due to preferential photo-cross-linking causes the molecular motion from the nonexposed to exposed region. , …”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…A similar molecular motion has been observed in the patterned exposure to cinnamate-containing polymeric films, which causes photo-cross-linking . The difference in the stiffness of the film due to preferential photo-cross-linking causes the molecular motion from the nonexposed to exposed region. , …”
Section: Resultssupporting
confidence: 54%
“…Photoinduced orientation in photosensitive polymeric films has the potential to realize molecularly oriented films, optical memories, and polarization-sensitive optical devises. Many types of photoalignable materials exhibiting photoinduced orientation based on axis-selective trans–cis–trans photoisomerization and/or photo-cross-linking have been explored using linearly polarized (LP) light and in some cases subsequent thermally stimulated self-organization. Among them, azobenzene-containing polymers have been intensively investigated due to their sufficient photoinduced orientation ability and rather clear photochemistry. , Moreover, surface relief (SR) formation without a wet process has often been observed in photoalignable materials when using patterned exposure and intensity/polarization holography. The molecular motion of the azobenzene moieties is generated due to a change in the thermal property from the liquid crystalline (LC) state to the isotropic state at the exposed region as well as the periodical change in the polarization state upon the photoinduced reorientation motion of the azobenzene moieties. Additionally, the periodical change in the stiffness of the photo-cross-linkable films generates a thermally induced molecular motion to form SR. …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] It is considered a potential option to fabricate nano-or micropatterns on material surfaces with no need of complicated procedures, in contrast to photolithography. Cis-trans photoisomerization of azobenzene has been mainly adopted for the formation of SR structures, while other mechanisms such as photochromic transformation of spiropyran 6 or spirooxazine 7 and photodimerization of anthracene 8 or cinnamate 9,10 have also been employed to create SR microstructures. It has been found that SR can be formed on the surface of various types of materials, including amorphous polymers, 11 liquid-crystalline polymers, 12 amorphous molecular materials, 13,14 and organic single crystals.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of photodimerization-based systems, concentration gradients of molecular species created by spatially patterned UV irradiation, in which the concentration of unreacted molecules becomes lower in the exposed region, and molecular diffusion (from unexposed region to exposed region) upon heating in the films seem to be at least part of the primary driving mechanisms of the SR structure formation. [8][9][10] These SR systems are characterized by their reversible structures that can be erased to recover their original flat surface by the exposure of the whole surface to UV, visible light, or by heating to higher temperatures above glass transition temperatures. This makes SR systems promising for rewritable optical devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation